A Study on the Polymorphism of Adalia bipunctata Ladybird in Maymana City, Faryab Province, Afghanistan - Niazyar, Azizullah; Hotak, Shamsullah; Saeedi, Ghani Dad (Universitas Pendidikan Nasional, 2025)
This research was conducted in the year 1400 (2021) in Maymana city, the center of Faryab province in northern Afghanistan. The sampling area was located within the geographic coordinates of 35°53'25.8